Testing the Random Movement of Shares in the Supply Chain of Some Sectors Listed In the Iraq Stock Exchange - Rahi AL-Hisnawi, Salim Sallal; Abd AL-Shara, Aqeel Shakir; Attieh Al - Bidairi, Karrar Hatam (International Journal of Supply Chain Management, 2018)
Abstract- The study aimed to identify random movements of shares in the supply chain of some sectors listed in the Iraqi market for securities using the daily data of the market index ISX60 to identify the level of efficiency of the market at the weak level, the study community is the financial market in general, while the study sample consisted of three sectors: the banking sector included 6 companies, the telecommunications sector included 1 company, and the hotel sector, which included 3 companies. To analyze and test the hypotheses of the study, three tests were used: Variance Ratio, Runs, and Serial Correlation, by R statistics program, for the period from 1/1/2015 to 31/12/2017. The study concluded that the returns of the ISX60 index in the Iraqi market for securities do not follow the random behavior in general, which means the inefficiency of the Iraqi market for securities within the weak level of efficiency, except the variable range test. The study recommended the activation of market activities to remove the possibility of extraordinary returns by investors through the disclosure and access of information to all investors to increase the efficiency of the supply chain of Iraqi financial market.